Fluktuasi Populasi dan Tingkat Kerusakan Akibat Serangan Thrips (Thysanoptera) pada Terong (Solanum Melongena L.) di Lingkungan Greenhouse - Muhammad Akram Holis; Hery Hariyanto; Amrul Jihadi (Universitas Khairun, 2026)
Eggplant (Solanum melongena L.) is a horticultural commodity with high economic value that is widely cultivated in greenhouse environments. Although the microclimate conditions in greenhouses can be adjusted, thrips (Thysanoptera) attacks remain a problem because they can damage plants and reduce production yields. This study aims to identify thrips species that attack eggplant plants, analyze population dynamics, and determine the level of damage caused by thrips attacks in greenhouses. The study was conducted using a survey method with direct observation techniques on 30 sample plants selected by purposive systematic sampling and indirectly using yellow sticky traps. Population observations were carried out by counting nymphs and adults on sample plants and counting the number of thrips individuals in yellow sticky traps, while the level of damage was analyzed based on the intensity of attacks during eight weeks of observation. The results showed that there were four thrips species found, namely Thrips palmi, Frankliniella occidentalis, Thrips tabaci, and Frankliniella intonsa with a total population of 5,245 individuals. Thrips palmi was the species with the highest population, with 1,628 individuals (31.04%), followed by F. occidentalis with 1,512 individuals (28.83%). The thrips population increased from the beginning of observations, peaking in the fourth week before gradually declining. Attack intensity fluctuated, with the lowest average attack rate of 8.42% in the first week and the highest at 10.20% in the third week.